Pemanfaatan Penilaian Otentik Berbasis Kemandirian Siswa dalam Pembelajaran Sejarah - Hasibuan, Risdam Habibi (Medan Resource Center, 2023)
Independent learning is a type of learning in which students must complete authentic assessments based on their own initiative. As a result, various approaches to developing quality history learning steps and a Pancasila profile in relation to independent schools with student autonomy are required. The development of history learning can be accomplished through three methods of implementing the social profile: teaching resources, learning methods, and authentic assessment. The use of authentic assessment will encompass the selection of instructional materials and learning models, making it a significant channel. Authentic assessment guides learning by allowing students to create various learning activities that contain the Pancasila Profile's contents during the learning process. Authentic assessment provides a true picture of students' reading abilities as well as a measure of their progress toward independence. As a result of this fact, authentic assessment can aid in the improvement of history learning as well as the development of student independence.